2007
DOI: 10.1007/s10964-007-9253-8
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Resolution in Mexican American Adolescents’ Friendships: Links with Culture, Gender and Friendship Quality

Abstract: This study was designed to describe the conflict resolution practices used in Mexican American adolescents' friendships, to explore the role of cultural orientations and values and gender-typed personality qualities in conflict resolution use, and to assess the connections between conflict resolution and friendship quality. Participants were 246 Mexican American adolescents (M = 12.77 years of age) and their older siblings (M = 15.70 years of age). Results indicated that adolescents used solution-oriented stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…In this case, it appears that the internalization of the cultural value of placing the family above the individual is associated with a behavioral approach to managing conflict. The findings of Killoren et al (2008) & Thayer et al (2008) portray Mexican American adolescents as active in conflict resolution and seem to contradict the Schofield et al (2008) finding that Mexican American adolescents are less likely to use direct eye contact with their parents. Rather it is possible that expressions of conflict behavior may differ based on the adolescent’s relationship to the conflict partner (sibling versus parent), thus, having different cultural meanings and consequences for how conflict is resolved within families.…”
Section: Individual Family and Cultural Predictors Of Support Seekingmentioning
confidence: 57%
See 1 more Smart Citation
“…In this case, it appears that the internalization of the cultural value of placing the family above the individual is associated with a behavioral approach to managing conflict. The findings of Killoren et al (2008) & Thayer et al (2008) portray Mexican American adolescents as active in conflict resolution and seem to contradict the Schofield et al (2008) finding that Mexican American adolescents are less likely to use direct eye contact with their parents. Rather it is possible that expressions of conflict behavior may differ based on the adolescent’s relationship to the conflict partner (sibling versus parent), thus, having different cultural meanings and consequences for how conflict is resolved within families.…”
Section: Individual Family and Cultural Predictors Of Support Seekingmentioning
confidence: 57%
“…For instance, when Mexican American adolescents show a more familistic orientation they also tend to use more active and solution-oriented conflict strategies for conflict resolution, regardless of whether the conflict partner was a sibling (Killoren, Thayer, & Updegraff, 2008) or friend (Thayer, Updegraff, & Delgado, 2008). In this case, it appears that the internalization of the cultural value of placing the family above the individual is associated with a behavioral approach to managing conflict.…”
Section: Individual Family and Cultural Predictors Of Support Seekingmentioning
confidence: 99%
“…For instance, one study found that adolescents who are higher in empathy use more compromising strategies, are more likely to discuss issues with friends, and are less likely to become angry when resolving conflicts with friends (de Wied, Branje, & Meeus, 2007). Furthermore, because better conflict resolution strategies are related to lower friendship discord during adolescence (Thayer, Updegraff, & Delgado, 2008), we argued that adolescents who were higher in empathy would demonstrate greater conflict management competence, which would lead to less friendship conflict (Hypothesis 1b).…”
Section: Mediating Role Of Interpersonal Competencementioning
confidence: 97%
“…Observational studies of such specific friendship processes would provide a better sense of what happens when one friend " crosses the line " and engages in behavior that damages, rather than enhances, the relationship. Little is known about the specific relationship repair mechanisms that adolescents enact to allow relationships to continue after conflicts, although there has been some effort in self -report studies to explore common conflict resolution strategies that adolescents employ (Thayer, Updegraff, & Delgado, 2008 ).…”
Section: Other Process Issuesmentioning
confidence: 99%